2022
DOI: 10.3389/fcell.2022.788587
|View full text |Cite
|
Sign up to set email alerts
|

The Roles of EphB2 in Cancer

Abstract: The erythropoietin-producing hepatocellular carcinoma (Eph) receptors and their Eph receptor-interacting (ephrin) ligands together constitute a vital cell communication system with diverse roles. Experimental evidence revealed Eph receptor bidirectional signaling with both tumor-promoting and tumor-suppressing activities in different cancer types and surrounding environment. Eph receptor B2 (EphB2), an important member of the Eph receptor family, has been proved to be aberrantly expressed in many cancer types,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 120 publications
(198 reference statements)
4
18
0
Order By: Relevance
“…PET1 alone did not cause phosphorylation of any RTKs, suggesting that the peptide does not cause off-target effects. We observed that after EGF treatment, EGFR was heavily phosphorylated (red) as expected, and EGFR co-receptors showed increased phosphorylation including ErbB2/Her2 (orange), ErbB3/HER3 (purple), MerTK (green), and EphB2 (yellow) (35)(36)(37). Interestingly, while EGFR phosphorylation was not sensitive to the presence of the peptide, phosphorylation of MerTK and EphB2 appeared to show a decrease with EGFR+PET1 treatment.…”
Section: Pet1 Co-localizes With and Binds To Egfrsupporting
confidence: 71%
“…PET1 alone did not cause phosphorylation of any RTKs, suggesting that the peptide does not cause off-target effects. We observed that after EGF treatment, EGFR was heavily phosphorylated (red) as expected, and EGFR co-receptors showed increased phosphorylation including ErbB2/Her2 (orange), ErbB3/HER3 (purple), MerTK (green), and EphB2 (yellow) (35)(36)(37). Interestingly, while EGFR phosphorylation was not sensitive to the presence of the peptide, phosphorylation of MerTK and EphB2 appeared to show a decrease with EGFR+PET1 treatment.…”
Section: Pet1 Co-localizes With and Binds To Egfrsupporting
confidence: 71%
“…In hepatocellular carcinoma, EPHB2 enhances cancer stem cell properties and drive sorafenib resistance by activating SRC/AKT/GSK3β/β-catenin signaling cascade. Moreover, EPHB2 mediated malignant progression of medulloblastoma by regulating ERK, P38 and mTOR pathway ( 37 , 38 ). Although studies have shown that EPHB2 is involved in the malignant progression of various cancers, its role in LUAD has yet to be investigated ( 37 ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, EPHB2 mediated malignant progression of medulloblastoma by regulating ERK, P38 and mTOR pathway ( 37 , 38 ). Although studies have shown that EPHB2 is involved in the malignant progression of various cancers, its role in LUAD has yet to be investigated ( 37 ). In the present study, we found that EPHB2 was closely associated with malignant progression of LUAD, promoting proliferation, invasion and migration of LUAD cells.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we adopted the approach of text mining and bioinformatics, and finally, four potential genes (EPHB2, SPP1, SERPINE1, and VEGFC) were found. The erythropoietin-producing hepatocellular carcinoma receptor B2 (EPHB2), an essential member of the erythropoietin-producing hepatocellular carcinoma (EPH) receptor family, has been confirmed to be highly expressed in various tumors, such as breast cancer, meningioma, colorectal cancer, gastric cancer, and lung cancer [22]. High expression of EPHB2 is considered a proto-oncogene by promoting blood vessel formation by enhancing cancer cell motility, invasion, and metastasis.…”
Section: Discussionmentioning
confidence: 99%